Values characteristics of Chinese college students with upper-level learning engagement - Tang, Songge; Gao, Di (Frontiers in Psychology, 2025)
IntroductionCurrently, much of the research on learning engagement has more underlined the individual factors associated with levels of learning engagement among college students, but the connections between individual values and learning engagement has not been definitively elucidated. The aim of this research is to reveal the relationships between individual values preferences and degrees of learning engagement, and mainly focuses on the individual values preferences of Chinese college students with upper-level learning engagement.MethodsData from 360 first-year Chinese college students majored in foreign languages in Northeast China supported a two-cluster of students based on different learning engagement levels. The assignment of items in the UWES-S scale and the PVQ-21 scale was confirmed through a principal component method to identify the underlying dimensions of Chinese college students’ learning engagement and values. A cluster analysis with K-means algorithm to cluster the participants based on their learning engagement levels. And a series of One-Way Analyses of Variance (ANOVAs) were performed to assess the differences between the cluster groups in relation to each of the values and mainly analyzed individual values characteristics of students with upper-level learning engagement.ResultsComparing values preferences of students with upper-level learning engagement and those with lower-level learning engagement, the results showed that students with upper-level learning engagement assigned more importance to “Social Focus” values, “Openness to Change” values, benevolence, and hedonism. Which presents a promising opportunity for future research to explore the potential impact of values education on students’ learning engagement.ConclusionThis research enhances the comprehension of the intricate relationship between learning engagement and values and offers a potential avenue for further investigation into the potential impact of values education on students’ learning engagement.